Independent Predictors of Human Milk Receipt at Neonatal Intensive Care Unit Discharge - Brownell, Elizabeth A.; Lussier, Mary M.; Hagadorn, James I.; McGrath, Jacqueline M.; Marinelli, Kathleen A.; Herson, Victor C. (American Journal of Perinatology, 2014)
Objective The aim of this study is to construct a predictive model for very low birth weight (VLBW) infants' receipt of mother's own milk within 24 hours before neonatal intensive care unit (NICU) discharge.Study Design Vermont Oxford Network (VON) clinical data were analyzed retrospectively for VLBW infants admitted between 2002 and 2012 at an inner city, level IV NICU with a well-established lactation program. Bivariate analyses compared infant characteristics between recipients and nonrecipients of human milk before 24 hours of NICU discharge. Independent predictors identified in the bivariate analyses (p ≤ 0.05), were eligible for inclusion into a multivariable logistic regression model.Results We observed a 60.4% human milk feeding rate at NICU discharge. Multiple independent maternal (black race and Hispanic ethnicity) and clinical factors (need for mechanical ventilation, patent ductus arteriosus, late-onset sepsis, or discharge to home on a cardiorespiratory monitor) positively predicted the outcome.Conclusions Our results were inconsistent with previous studies and suggest that a strong NICU lactation program in combination with a community-based peer counselor program may increase rates of human milk receipt among VLBW infants born to black/Hispanic mothers and those with more complicated neonatal courses.
Keywords: Vermont Oxford Network; neonatal intensive care units; breast milk expression; lactation; patient acuity; perinatology; neonatology